Varietal Evaluation of date palm (Phoenix dactylifera L.) in Kachchh, India - Sharma, Kapil Mohan; Muralidharan, C. M.; Baidiyavadra, D. A.; Panchal, C. N.; Verma, Piyush (Journal of Plantation Crops, 2020)
Date palm (Phoenix dactylifera L.) is one of the important fruit crops of semi-arid regions of the western border of India with Kachchh district of Gujarat comprising of the highest area and production. The majority of the plantations in this area are seed propagated, resulting in high variability and irregular orchards. For systematic planting, a variety of desired quality is required for which this experiment was laid out in 2007 to evaluate five promising varieties viz., Barhee, Halawy, Khunezi, Khalas and Selection-3 in an RBD design, replicated four times. Evaluation of all these varieties was done during 2016-18 when all the plants came into regular bearing. Observations with respect to vegetative characters, yield attributing characters, duration of fruit harvesting and fruit characters were recorded and finally varieties were compared with a scorecard to identify the best variety for commercial cultivation. After the evaluation, it was found that Barhee performed best among the cultivars compared and is suitable for commercial cultivation in the Gujarat state of India.